2021
DOI: 10.3389/fimmu.2020.613745
|View full text |Cite
|
Sign up to set email alerts
|

Detection of In Vivo Inflammasome Activation for Predicting Sepsis Mortality

Abstract: Sepsis is a severe life-threatening syndrome caused by dysregulated host responses to infection. Biomarkers that allow for monitoring the patient’s immune status are needed. Recently, a flow cytometry-based detection of in vivo inflammasome activation by formation of cytoplasmic aggregates of ASC (apoptosis-associated speck-like protein containing a caspase recruitment domain) has been proposed. Here we report on the frequency of ASC-speck+ leukocytes correlating with the survival of sepsis. 25 patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…These findings support the possibility that both neutrophils and monocytes contribute to the cytokine storm through the inflammasome, and in vivo ASC-speck detection could serve as an indicator of innate immune system activation. In bacterial sepsis, Cui et al has shown that assessing ASC speck positive immune cells by flow cytometry could be used as a potential biomarker of patients at risk of death 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the possibility that both neutrophils and monocytes contribute to the cytokine storm through the inflammasome, and in vivo ASC-speck detection could serve as an indicator of innate immune system activation. In bacterial sepsis, Cui et al has shown that assessing ASC speck positive immune cells by flow cytometry could be used as a potential biomarker of patients at risk of death 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is an ideal tool for the clearance of infected cells because it is a form of lytic cell death that causes release of abundant inflammatory cytokines and enables destruction of intracellular replicative niches. This might be the positive role of pyroptosis in infection, but if out of control, it could be detrimental to the host [21][22][23][24]. Pyroptosis contributes to the hyperinflammatory response in sepsis, and recent advances indicate its role in adaptive immunity, which is closely related to immune paralysis.…”
Section: What Do We Know About Pyroptosis In Sepsismentioning
confidence: 99%
“…When evaluating ASC-speck formation in monocytes during the first week of sepsis in patients, the highest number of ASC-speck + monocytes can be detected on day 6-7. Survival analysis shows that patients with lower numbers of ASC-speck + monocytes (<1650 cells/mL) on day 6 has greater risk of mortality [60].…”
Section: Elements Of Immunopathogenesis and Molecular Signature Of Se...mentioning
confidence: 99%